Perbandingan Pushover dan Pengujian Siklik pada Coupling Beam dan Link Geser dalam Struktur Baja - Intan Nuriskha Rachma; Eko Walujodjati (Jurnal Konstruksi, 2023)
The concept of earthquake resistant buildings is based on the yield mechanism in one element. In the steel frame structure core system, the coupling beam functions as an earthquake energy dissipation element where yielding is planned. However, if these elements are damaged, repair costs will be high and the process will disrupt building activities. Considering these conditions, the coupling beam element was developed by adding a sliding link. The yield mechanism is transferred to the link element while the coupling beam remains elastic. Numerical and experimental studies were carried out to review the yielding behavior that occurs in the link and coupling beam elements. The sub-assembly consisting of the column, coupling beam and shear link WF150x75x6x8 was tested under cyclic loading in accordance with AISC 341-10. Numerical analysis is carried out using a pushover method where parameters related to the non-linear properties of each sub-assembly are designed based on the provisions of FEMA-356. The pushover and experimental analysis results show that yielding can be maintained in the link. Cyclic testing on the Sub-assembly produces plastic rotation of the shear link of 0.17 radians without causing damage to the column and coupling beam. The first yield in the pushover analysis occurred at a force of 180.9 kN, while the experimental results occurred at a loading of 157.04 kN. Cyclic testing shows an increase in shear capacity of 7% from the results of the pushover analysis.